2018
DOI: 10.1016/j.jcrs.2018.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Acute-onset postoperative endophthalmitis after cataract surgery and transzonular intravitreal triamcinolone–moxifloxacin

Abstract: Postoperative endophthalmitis can occur after dropless cataract surgery with intravitreal triamcinolone-moxifloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…For example, dropless cataract surgery may need reconsideration in this age group because it is unclear whether intraocular moxifloxacin levels are maintained above the MIC sufficiently long enough to fully eradicate any antibiotic-resistant staphylococci that may breach the surgical wound 59,60 ; in this regard, there have been reports of endophthalmitis after dropless cataract surgery with moxifloxacin. [61][62][63][64] Of importance, of methicillin-resistant staphylococci sourced from vitreous or aqueous humor in this study, 91% of MRSA isolates and 71% of methicillin-resistant CoNS isolates had concurrent resistance to moxifloxacin (eAppendix, eFigure 2, and eFigure 3 in the Supplement). An increasing prevalence of resistance to antibiotics, especially fluoroquinolones, with patient age has also been reported by other researchers.…”
Section: Discussionmentioning
confidence: 83%
“…For example, dropless cataract surgery may need reconsideration in this age group because it is unclear whether intraocular moxifloxacin levels are maintained above the MIC sufficiently long enough to fully eradicate any antibiotic-resistant staphylococci that may breach the surgical wound 59,60 ; in this regard, there have been reports of endophthalmitis after dropless cataract surgery with moxifloxacin. [61][62][63][64] Of importance, of methicillin-resistant staphylococci sourced from vitreous or aqueous humor in this study, 91% of MRSA isolates and 71% of methicillin-resistant CoNS isolates had concurrent resistance to moxifloxacin (eAppendix, eFigure 2, and eFigure 3 in the Supplement). An increasing prevalence of resistance to antibiotics, especially fluoroquinolones, with patient age has also been reported by other researchers.…”
Section: Discussionmentioning
confidence: 83%
“…reported four cases (0.25%) of acute-onset postoperative endophthalmitis after uneventful temporal clear corneal topical dropless cataract surgery involving intravitreal triamcinolone-moxifloxacin drug combination (TriMoxi). [ 27 ] A similar study by Tyson et al . reported no incidence of endophthalmitis in a series of 1541 eyes.…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, the dropless cataract surgery studies have demonstrated that the incidence of post cataract surgery endophthalmitis is similar to that of conventional phacoemulsification surgery where the incidence is 0.04%–0.2%. [ 27 ] This raises the question of whether these studies are good enough to prove that dropless cataract surgery is as safe as conventional phacoemulsification surgery. The answer is probably not.…”
Section: Discussionmentioning
confidence: 99%
“…3 Unlike TA, the duration of intraocular moxifloxacin levels that exceed minimum inhibitory concentration (MIC) is relatively short after intravitreal administration and may predispose to possible infection. 7 We report a case of delayed-onset endophthalmitis following dropless cataract surgery with intravitreal Tri-Moxi. We conjecture that a fourth-generation fluoroquinolone-resistant organism (staphylococcus epidermidis) was inoculated into the eye during cataract surgery.…”
Section: Discussionmentioning
confidence: 95%
“…3 Unlike TA, the duration of intraocular moxifloxacin levels that exceed minimum inhibitory concentration (MIC) is relatively short after intravitreal administration and may predispose to possible infection. 7…”
Section: Discussionmentioning
confidence: 99%